Circadian Rhythms Coordinated With Gut Microbiota Partially Account for Individual Differences in Hepatitis B-Related Cirrhosis - Wang, Tongyao; Rong, Xingyu; Zhao, Chao (Frontiers in Cellular and Infection Microbiology, 2022)
Cirrhosis is the end stage of chronic liver diseases like chronic hepatitis B. In China, hepatitis B accounts for around 60% of cases of cirrhosis. So far, clinical and laboratory indexes for the early diagnosis of cirrhosis are far from satisfactory. Nevertheless, there haven’t been specific drugs for cirrhosis. Thus, it is quite necessary to uncover more specific factors which play their roles in cirrhosis and figure out the possible therapeutic targets. Among emerging factors taking part in the initiation and progression of cirrhosis, gut microbiota might be a pivot of systemic factors like metabolism and immune and different organs like gut and liver. Discovery of detailed molecular mechanism in gut microbiota and gut liver axis leads to a more promising prospect of developing new drugs intervening in these pathways. Time-based medication regimen has been proofed to be helpful in hormonotherapy, especially in the use of glucocorticoid. Thus, circadian rhythms, though haven’t been strongly linked to hepatitis B and its complications, are still pivotal to various pathophysiological progresses. Gut microbiota as a potential effective factor of circadian rhythms has also received increasing attentions. Here, our work, restricting cirrhosis to the post-hepatitis B one, is aimed to summarize how circadian rhythms and hepatitis B-related cirrhosis can intersect via gut microbiota, and to throw new insights on the development of new and time-based therapies for hepatitis B-related cirrhosis and other cirrhosis.